2015
DOI: 10.5935/1676-2444.20150047
|View full text |Cite
|
Sign up to set email alerts
|

First detection of metallo-β-lactamases in nosocomial isolates ofPseudomonas aeruginosain Alagoas, Brazil

Abstract: The history of muscle biopsy dates back to 1860, when Duchenne first performed a biopsy on a patient with symptoms of myopathy (1) . Since then, the basic and clinical science of muscle and muscle disease has gone through three stages of development: the classical period, the modern stage and the molecular era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We speculate that the resistance mechanisms of the aztreonam-resistant isolates in this study may involve AmpC-type β-lactamases, Extended Spectrum Beta-Lactamases, and the MexAB-OrpM efflux pump. 7,22,23 The limitations of this study were the small number of isolates and lack of clonal relatedness information. Therefore, repetitive clones might have been present.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We speculate that the resistance mechanisms of the aztreonam-resistant isolates in this study may involve AmpC-type β-lactamases, Extended Spectrum Beta-Lactamases, and the MexAB-OrpM efflux pump. 7,22,23 The limitations of this study were the small number of isolates and lack of clonal relatedness information. Therefore, repetitive clones might have been present.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the study of Abaza et al 18 demonstrated that 73.3% of their 30 MBLPA isolates were resistant to aztreonam. Furthermore, the study of Barros et al 22 reported the IMP-type MBLPA isolates to be resistant to aztreonam. Notably, we observed that all of our aztreonam-resistant isolates were MDR.…”
Section: Discussionmentioning
confidence: 99%